Workplace social capital and mental health: a cross-sectional study among Iranian workers - Mojgan Firouzbakht; Aram Tirgar; Tuula Oksanen; Ichiro Kawachi; Karimollah Hajian-Tilaki; Maryam Nikpour; Susan Mouodi; Reza Sadeghian (BMC, 2018)
Abstract Background The psychosocial environment of the workplace has received less attention in terms of occupational health. Trust, social network and social cohesion at the workplace (that is, factors related to social capital) may have effects on employee health. Thus, the objective of this study was to examine the association between workplace social capital and mental health among Iranian workers. Methods In this cross-sectional study, data were obtained from 5 factories in Babol, Northern Iran, in 2016, where 280 workers responded to a survey on social capital at work and psychosocial distress. Results Approximately 23.6% of the workers had psychological distress, and 23.4% had low social capital in the workplace. There was a significant relationship between mental health and individual workplace social capital (p = 0.025) and aggregated workplace social capital (p = 0.027). After controlling for each individual's characteristics, the prevalence ratio of psychological distress was 2.11 (95% CI: 1.43-3.17) times higher among workers with low individual social capital, and low aggregated workplace social capital was associated with 2.64 (95% CI: 1.28-5.45) times higher odds of psychological distress. Conclusion Higher social capital is associated with a reduced risk of psychological distress. The promotion of social capital can be considered as a means to increase workplace mental health among workers.